FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI USAHATANI JAGUNG DI KECAMATAN SINDUE KABUPATEN DONGGALA - Jonh Tomy (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The objective of this study was to analyze the influence of factors such as land, fertilizer, labor and seed on the production of corn farming, as well as the amount of income derived from it. The experiment was conducted in the Sindue Subdistrict Donggala Regency. The research location was purposively determined with consideration that it is the center of corn production. Respondent sample were chosen using a simple random sampling technique. The number of respondents were 30 corn farmers. Data of the production factors was analyzed using the Cobb-Douglas while income data from corn farming using analysis of the revenue. Analysis results showed that the production factors including land, fertilizer, labor and seeds simultaneously had significant effect on corn production. The t test also showed significant effect of land, fertilizers and seeds partially on the corn production while labor was not significant. Farmers' income generated from the corn farming per hectare per cropping season was IDR 1.521.515,66.                                             Key Words : Corn farming, income, production.